ANALISIS POTENSI RELATIF PEREKONOMIAN SEKTOR PERTAMBANGAN DI PROVINSI KEPULAUAN BANGKA BELITUNG PERIODE TAHUN 2013–2019 - Harry Wibawa (JURNAL GEOMINERBA (JURNAL GEOLOGI, MINERAL DAN BATUBARA), 2021)
The Province of the Bangka Belitung Islands is a potential area in the mining sector, especially the mineral content of tin ore. To find out whether the mining sector or business field is included in the economic base group and is considered potential as a leading sector in the economy in The Province of the Bangka Belitung Islands, it is necessary to conduct a study of the mining sector through quantitative models of regional economic development planning, namely location quotient and shift share analysis. Based on the results of the analysis using the location quotient (LQ) approach during the analysis period (2013-2019), it shows that the average value of LQ for the mining sector in the aggregate as well as for the part of the mining sector, namely the metal ore mining subsector/field of business, mining and other quarrying, as well as business fields which are business processes that continue from mining activities such as for the non-metallic mineral processing industry and for the base metal processing industry, all of which have an average LQ value above 1. This indicates that mining is a the basic sector and has a major role in the economy of The Province of the Bangka Belitung Islands. While the results of the analysis using the shift share approach show that in the mining sector in aggregate has the fastest growth in the Province of the Bangka Belitung Islands at 4.04 trillion rupiah compared to the national average growth; base metal industry has a relatively faster growth than the growth of other business fields in the mining sector (Ps> 0); and metal ore mining has the highest competitiveness in regional market share (Ds> 0) compared to all other in The Province of the Bangka Belitung Islands, amounting to 0.667 trillion rupiah.